2021
DOI: 10.1136/neurintsurg-2021-017664
|View full text |Cite
|
Sign up to set email alerts
|

Three-month functional outcomes following endovascular thrombectomy during the first wave of the COVID-19 pandemic: a Canadian single-center cohort study

Abstract: BackgroundThe COVID-19 pandemic has disrupted acute stroke care logistics, including delays in hyperacute management and decreased monitoring following endovascular therapy (EVT). We aimed to assess the impact of the pandemic on 90-day functional outcome among patients treated with EVT.MethodsThis is an observational cohort study including all patients evaluated for an acute stroke between March 30, 2020 and September 30, 2020 (pandemic cohort) and 2019 (reference cohort) in a high-volume Canadian academic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…Our laboratory analysis was in accordance with these studies. When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our laboratory analysis was in accordance with these studies. When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ]. The modified Rankin Scale score, as a rank of functional independence after AIS, showed no difference between our groups, as previously reported [ 37 ], although some studies reported higher mortality rate in COVID-19 patients [ 25 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, MT in patients with acute severe COVID-19 infection could be complicated by diagnostic delays imposed by the fact that these patients are more likely to be sedated and intubated, thus impeding the early detection of neurological deterioration. Third, the COVID-19 pandemic compromised the application of well-established therapies and appears to be disruptive for acute stroke pathways 13–15. Stroke patients without respiratory symptoms of COVID-19 might not seek care at all, preferring to stay at home than taking the risk of getting exposed to SARS-CoV-2 at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, other centers that maintained a traditional protocol that uses CS as first choice, reserving GA for airway, respiratory or hemodynamic compromise, did not suffer an impact of the pandemic in functional outcome among EVT treated patients. 13…”
Section: Discussionmentioning
confidence: 99%